Vigilante Justice in Modern South Africa: A Post-Democracy Analysis - Maruma, Kholofelo (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2024)
Despite the establishment of democracy in South Africa, mob justice remains a pervasive and troubling issue. This study investigates the socio-economic and cultural factors that sustain this form of extrajudicial punishment, tracing its origins to historical injustices and contemporary dissatisfaction with the formal justice system. Through qualitative analysis of case studies and interviews, the research reveals that communities, often feeling neglected and insecure, resort to mob justice as a means of immediate retribution and deterrence. The findings highlight the urgent need for comprehensive reforms in law enforcement, community engagement, and social services to address the underlying causes of mob justice and restore confidence in the democratic legal framework. This paper advocates for a multi-faceted approach to eradicate this practice, emphasizing the importance of education, economic development, and robust legal protections to ensure justice and human rights for all citizens.